2011
DOI: 10.1063/1.3605703
|View full text |Cite
|
Sign up to set email alerts
|

Re-entrant phase behaviour of network fluids: A patchy particle model with temperature-dependent valence

Abstract: Abstract:We study a model consisting of particles with dissimilar bonding sites ("patches"), which exhibits self-assembly into chains connected by Y-junctions, and investigate its phase behaviour by both simulations and theory. We show that, as the energy cost epsilon(j) of forming Y-junctions increases, the extent of the liquid-vapour coexistence region at lower temperatures and densities is reduced. The phase diagram thus acquires a characteristic "pinched" shape in which the liquid branch density decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 58 publications
1
69
0
Order By: Relevance
“…However, it is significantly more challenging to control lattice transitions between different phases, crystallographic symmetries or morphological states, wherein global structural reorganization is required. One tentative example is to exploit peculiar temperature-dependent interactions, such as reentrant liquid-solid-liquid transitions, as recently studied theoretically 18,19 and experimentally 20,21 .…”
mentioning
confidence: 99%
“…However, it is significantly more challenging to control lattice transitions between different phases, crystallographic symmetries or morphological states, wherein global structural reorganization is required. One tentative example is to exploit peculiar temperature-dependent interactions, such as reentrant liquid-solid-liquid transitions, as recently studied theoretically 18,19 and experimentally 20,21 .…”
mentioning
confidence: 99%
“…This orientational order can also appear as a second phase transition for values of y < 0.5 where the LVE occurs. The topology of the empty liquid phases is well understood [9][10][11][12]. At low temperature (where the empty liquid regime occurs) and not too low density almost all the A patches are participating in a bond, and the liquid phases then can be described as a network fluid composed of (almost) straight chains of spheres linked by sequences of AA bonds.…”
mentioning
confidence: 99%
“…These systems sometimes present reentrant condensation induced by variations of salt concentration [5,6]. The mechanisms involved in the condensation and the dependence of the reentrant behavior with temperature are not well understood, but it is likely that specific (patchylike) interactions [7,8] play an important role.Given the complexity of both kinds of problems, selfassembly of patchy colloids and the phase behavior of protein solutions, it seems important to study simple models of the patchy particles in order to understand the influence of the numbers of patches and their distribution on the phase behavior and aggregation mechanisms of complex systems.Recently it has been found that patchy models with two types of patches, A and B, in which only A-A and A-B interactions are attractive, can exhibit liquid-vapor equilibria (LVE) with liquid phases behaving as "empty liquids" [9][10][11]. For these systems the term "empty liquid" [4] refers to the fact that at low temperatures the density of the liquid phase ρ L on the binodal becomes very small at low temperature.…”
mentioning
confidence: 99%
“…There has also been an extensive number of theoretical and simulation studies on the thermodynamics, phase behavior, and self-assembly of patchy colloid fluids. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Patchy colloids are typically modeled using Wertheim's first order perturbation theory (TPT1) and a potential model for conical association sites introduced by Bol 22 and later Chapman 23 that became widely used in the patchy colloid community after Kern and Frenkel 24 introduced this potential as a primitive model for patchy colloids. a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%